Estimation of the Manufacturing Product Complexity Based on the Product Information on Turning Process Product - Romiyadi, Romiyadi; Azriadi, Emon (-)
Product complexity index was an indicator of a manufacturing product that describes the products are designed and manufactured with a level of complexity. In this study, assesment of product complexity was conducted on milling processing product. Assesment conducted on the variable of turning processing product complexity based on features of the products and specifications of materials, shapes, geometry, tolerance, general surface finish and hardness. ElMaraghy introduced the method in this study and Urbanic based on information product were absolute quantity information, diversity of information, and content of product information. The results of product complexity assesment indicated that the product of original External Thread Bearing Housing had product complexity index of 6.28. While the results of product complexity assesment indicated that, the product of redesign External Thread Bearing Housing had product complexity index of 8.96.